Ravenloft : Heir of Strahd - Dawson, Delilah S. (Dungeons & Dragons, 2025)
"A party of adventurers must brave the horrors of Ravenloft in this official Dungeons & Dragons novel! Five strangers armed with steel and magic awaken in a mist-shrouded land, with no memory of how they arrived: Rotrog, a prideful orcish wizard; Chivarion, a sardonic drow barbarian; Alishai, an embittered tiefling paladin; Kah, a skittish kenku cleric; and Fielle, a sunny human artificer. After they barely survive a nightmarish welcome to the realm of Barovia, a carriage arrives bearing an invitation: Fairest Friends, I pray you accept my humble Hospitality and dine with me tonight at Castle Ravenloft. It is rare we receive Visitors, and I do so Endeavor to Make your Acquaintance. The Carriage shall bear you to the Castle safely, and I await your Arrival with Pleasure. Your host, Strahd von Zarovich With no alternative, and determined to find their way home, the strangers accept the summons and travel to the forbidding manor of the mysterious count. But all is not well at Castle Ravenloft. To survive the twisted enigmas of Strahd and his haunted home, the adventurers must confront the dark secrets in their own hearts and find a way to shift from strangers to comrades-before the mists of Barovia claim them forever"--